Proinflammatory cytokines as serum biomarker in oral carcinoma—A prospective multi‐biomarker approach. (22nd January 2018) - Schiegnitz, Eik; Kämmerer, Peer W.; Schön, Holger; Blatt, Sebastian; Berres, Manfred; Sagheb, Keyvan; Al‐Nawas, Bilal
Abstract : Background: Inflammation and cell‐mediated immunity have a key role in different stages of carcinogenesis. The aim of this prospective study was to assess serum levels of proinflammatory cytokines interleukin‐6 (IL‐6), interleukin‐8 (IL‐8), soluble interleukin‐2 receptor (sIL‐2R), tumor necrosis factor alpha (TNF‐α), and MHC class I polypeptide‐related sequence B (MICB) in patients with oral premalignant lesion (OPL), oral squamous cell carcinoma (OSCC), and healthy controls in a multi‐biomarker approach as a potential diagnostic and prognostic tool for OSCC. Material and Methods: A total of 205 patients (81 with OSCC, 75 with OPL, and 49 healthy controls) were included in this prospective study. Cytokine concentrations were measured by commercial enzyme linked immunoassay and chemiluminescence immunoassay. Results: IL‐6, IL‐8, and sIL‐2R were significantly elevated in OSCC patients compared to healthy controls and to OPL patients. Higher T‐Grade (>T2) and positive lymph node involvement resulted in significantly higher IL‐6 values ( P < .001 and P = .037). IL‐6 serum values ≥5 pg/mL (n = 45) and sIL‐2R serum values ≥623 U/mL (n = 19) indicated a significant lower survival rate compared to OSCC patients with low IL‐6 (n = 36) and sIL‐2R values (n = 62, P = .023 and P = .026). ROC and classification tree analyses identified the combination of IL‐6 and IL‐8 as diagnostic markers with good diagnostic accuracy. Conclusion: In conclusion, IL‐6, IL‐8, and sIL‐2R are strongly associated with OSCC oncogenesis and IL‐6 and sIL‐2R seem to be promising and potent biomarkers for evaluating patients' prognosis.